Positive and Negative Risk-Taking in Adolescence and Early Adulthood: A Citizen Science Study During the COVID-19 Pandemic - te Brinke, Lysanne W.; van der Cruijsen, Renske; Green, Kayla H.; Crone, Eveline A. (Frontiers in Psychology, 2022)
Sensation seeking is an important underlying factor of both positive and negative forms of risk-taking during adolescence and early adulthood. However, macro-factors such as the global Covid-19 pandemic may influence sensation seeking opportunities and risk-taking behaviors that are considered negative and positive. Therefore, the primary aim of this study was to examine the associations between sensation seeking and behaviors that are considered positive or negative forms of risk-taking during the Covid-19 pandemic in a sample of adolescents and early adults (N = 660, Mage = 22.91, SD = 3.14). Using citizen science methods, negative risk-taking was defined as taking unaccepted risks, such as falsifying vaccination reports or deliberately contracting Covid-19. Positive risk-taking was defined as taking socially accepted risks, such as balancing between the risk to infect elderly people and the need to socialize with peers. Results showed that participants with higher levels of sensation seeking took more positive and negative Covid-19 related risks. An additional finding was that sensation seeking was positively associated with the need to contribute to society. This indicates that during adolescence and early adulthood, sensation seeking may be a driving factor for both positive (i.e., socially accepted) and negative (i.e., socially unaccepted) risk-taking in the context of a high-stake global pandemic, arguing against a one-direction negative relation between sensation seeking and risk-taking.